PENGARUH KONSENTRASI ZAT PENGATUR TUMBUH GIBERELIN TERHADAP VIABILITAS BENIH PALA (Myristica fragrans) PADA MEDIA COCOPEAT - Helen Priscilia Lunmisay; Andjela Sahupala; Ludia Siahaya (MARSEGU : Jurnal Sains dan Teknologi, 2026)
Nutmeg (Myristica fragrans Houtt.) is one of the leading spice commodities of Maluku with high economic value. However, its productivity has declined due to the aging of many nutmeg plantations. One effort to improve the availability of high-quality seedlings is through enhancing seed germination success. This study aimed to determine the effect of gibberellin application on the viability and germination of nutmeg seeds grown in cocopeat medium. The research was conducted at the Experimental Garden of the Department of Forestry, Pattimura University, from April to May 2026. A Completely Randomized Design (CRD) was employed with four gibberellin concentration treatments: 0 ppm (A0), 25 ppm (A1), 50 ppm (A2), and 75 ppm (A3), each replicated three times. Nutmeg seeds were soaked in gibberellin solutions for 3 hours before being sown in cocopeat medium. The observed parameters included germination percentage, germination rate, and Mean Germination Time (MGT). Data were analyzed using Analysis of Variance (ANOVA) at a 5% significance level. The results showed that gibberellin application had a highly significant effect on all observed parameters. The A2 treatment (50 ppm) was identified as the optimum concentration, resulting in the highest germination percentage (100%), the highest germination rate (1.66), and the lowest MGT value (6.47 days). Therefore, the application of 50 ppm gibberellin in cocopeat medium is recommended to improve seed viability and accelerate the germination of nutmeg seeds.